Spousal Relationship, Gender and COVID -19 Outbreak in South Korea - Choi, Seulki; Joung, Eunhee; Choi, Saeeun; Ko, Kwangman (KDI School of Public Policy and Management, 2022)
Drawing upon the Process-Person-Context-Time (PPCT) model, this study examines how people in South Korea perceived their spousal relationships under COVID-19 outbreak. Analyzing 720 married respondents with a young child from the Survey on Koreans’ set of values regarding marriage and family in the COVID-19 era conducted on February 2021, we found that the majority of the respondents did not experience any change, and this was more pronounced in men. Infection concern and income decrease were universal factors causing negative influence on spousal relationships. Meanwhile, results of this study show sharing housework was important to women’s perceived relationship quality, which may reflect the gendered division of housework in South Korea. It implies that the threats from outside like COVID-19 fail to hurt spousal relationship in South Korea. On the contrary, it makes the relationship stronger.
Keywords: COVID-19; Gender; Spousal Relationship; PPC